Mechanisms for Progenitor Cell-Mediated Repair for Ischemic Heart Injury - Calvin Li, Shengwen; Acevedo, Julyana; Wang, Lang; Jiang, Hong; Luo, Jane; G. Pestell, Richard; G. Loudon, William; C. Chang, Anthony (Current Stem Cell Research & Therapy, 2012)
Recent studies have shown that treatments involving injection of stem cells into animals with damaged cardiac tissue result in improved cardiac functionality. Clinical trials have reported conflicting results concerning the recellularization of post-infarct collagen scars. No clear mechanism has so far emerged to fully explain how injected stem cells, specifically the commonly used mesenchymal stem cells (MSC) and endothelial precursor cells (EPC), help heal a damaged heart. Clearly, these injected stem cells must survive and thrive in the hypoxic environment that results after injury for any significant repair to occur. Here we discuss how ischemic preconditioning may lead to increased tolerance of stem cells to these harsh conditions and increase their survival and clinical potential after injection. As injected cells must reach the site in numbers large enough for repair to be functionally significant, homing mechanisms involved in stem cell migration are also discussed. We review the mechanisms of action stem cells may employ once they arrive at their target destination. These possible mechanisms include that the injected stem cells (1) secrete growth factors, (2) differentiate into cardiomyocytes to recellularize damaged tissue and strengthen the post-infarct scar, (3) transdifferentiate the host cells into cardiomyocytes, and (4) induce neovascularization. Finally, we discuss that tissue engineering may provide a standardized platform technology to produce clinically applicable stem cell products with these desired mechanistic capacities.
Keywords: precursor cells